Utilitarianisme Menurut John Stuart Mill dan Relevansinya Bagi Aktivitas Ekonomi : Perspektif Filsafat Ekonomi - Lermatan, Petrus (Jurnal Seri Mitra (Refleksi Ilmiah Pastoral), 2024)
The aim of this article is to explain John Stuart Mill’s thought of utilitarianism and to attract its relevance in doing economics activity. Using descriptive and analytical methods this study finds that although Mill based his theory on the utilitarianism of Bentham he then developed and applied it widely in politics and economics. According to Mill, an act can be considered ethical if intended to increase the happiness of many people and since the purpose of life is for the happiness of many people, one should have willingness to sacrifice himself and act wisely to contribute the happiness of all. Here, utilitarianism of Mill offers moral guideline for society in economics activities hence can be used and applied to every economics activity so that bring great happiness to many people.